Alzheimer disease seen through the lens of sex and gender - Castro-Aldrete, Laura; Einsiedler, Melanie; Novakova Martinkova, Julie; Depypere, Herman; Alvin Ang, Ting Fang; Mielke, Michelle M; Sindi, Shireen; Eyre, Harris A; Au, Rhoda; Schumacher Dimech, Anne Marie; Dé, Anna; Szoeke, Cassandra; et al. (Nature reviews. Neurology, 2025)
Alzheimer disease (AD) is a life-limiting neurodegenerative disorder that disproportionately affects women. Indeed, sex and gender are emerging as crucial modifiers of diagnostic and therapeutic pathways in AD. This Review provides an overview of the interactions of sex and gender with important developments in AD and offers insights into priorities for future research to facilitate the development and implementation of personalized approaches in the shifting paradigm of AD care. In particular, this Review focuses on the influence of sex and gender on important advances in the treatment and diagnosis of AD, including disease-modifying therapies, fluid-based biomarkers, cognitive assessment tools and multidomain lifestyle interventional studies.
Keywords: sexuální faktory; mužské pohlaví; Alzheimerova nemoc; ženské pohlaví; Alzheimer Disease; Humans; Biomarkers; pohlavní dimorfismus; Female; Sex Factors; biologické markery; Sex Characteristics; lidé; Male